Frictional Instabilities and Carbonation of Basalts Triggered by Injection of Pressurized H(2)O‐ and CO(2)‐ Rich Fluids - Giacomel, Piercarlo (Geophys Res Lett, 2018)
The safe application of geological carbon storage depends also on the seismic hazard associated with fluid injection. In this regard, we performed friction experiments using a rotary shear apparatus on precut basalts with variable degree of hydrothermal alteration by injecting distilled H(2)O, pure CO(2), and H(2)O + CO(2) fluid mixtures under temperature, fluid pressure, and stress conditions relevant for large‐scale subsurface CO(2) storage reservoirs. In all experiments, seismic slip was preceded by short‐lived slip bursts. Seismic slip occurred at equivalent fluid pressures and normal stresses regardless of the fluid injected and degree of alteration of basalts. Injection of fluids caused also carbonation reactions and crystallization of new dolomite grains in the basalt‐hosted faults sheared in H(2)O + CO(2) fluid mixtures. Fast mineral carbonation in the experiments might be explained by shear heating during seismic slip, evidencing the high chemical reactivity of basalts to H(2)O + CO(2) mixtures.